Evaluación del potencial antimicrobiano del extracto de cáscara, semilla y pulpa de la Vitis vinífera sobre el cultivo de S. mutans (2024)
ABSTRACT Introduction: In the ongoing search for novel natural agents with potential health benefits, phenolic compounds have garnered significant attention due to their demonstrated antimicrobial and anti-inflammatory properties. Among these compounds, resveratrol and flavonoids, which are abundant in various plant sources, have shown promise in combating microbial infections and reducing inflammation. Materials and Methods: Three types of extracts were evaluated: One commercial and two experimental (aqueous and hydroalcoholic), prepared from the peel, seed, and pulp of Vitis vinifera. Two different dehydration temperatures were used. The S. mutans strain was selected and cultured on BHI agar plates, which were then treated with the extracts. Inhibition zones were measured at various times, with 0.2% chlorhexidine used as a positive control and sterile saline solution as a negative control. Results. No inhibition zones were found for any of the commercial extracts or experimental. Only inhibition zones were observed in the positive control of Chlorhexidine. Conclusions. The commercial extract and the hydroalcoholic and aqueous experimental extracts prepared from Vitis vinifera grape did not exhibit inhibition against S. mutans.